2001
DOI: 10.1136/fn.85.3.f214
|View full text |Cite
|
Sign up to set email alerts
|

Genetic determinants of bone mineral content in premature infants

Abstract: Genetic determinants of bone mineral content in prematurely born children at 3 months and 9-11 years of age were studied. The findings suggest that multiple genes are involved in the regulation of site specific bone mass accumulation during childhood. (Arch Dis Child Fetal Neonatal Ed 2001;85:F214-F216)

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2004
2004
2015
2015

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(2 citation statements)
references
References 14 publications
0
2
0
Order By: Relevance
“…Di George syndrome was excluded by negative FISH probe, resolution of hypocalcaemia and absent associated clinical features. Genetic differences in vitamin D receptor (VDR) alleles of the twins may explain variance, 7 if twin 1's VDR preferentially used meagre maternal vitamin D stores. No prenatal measurements of maternal calcium level were available.…”
Section: Discussionmentioning
confidence: 99%
“…Di George syndrome was excluded by negative FISH probe, resolution of hypocalcaemia and absent associated clinical features. Genetic differences in vitamin D receptor (VDR) alleles of the twins may explain variance, 7 if twin 1's VDR preferentially used meagre maternal vitamin D stores. No prenatal measurements of maternal calcium level were available.…”
Section: Discussionmentioning
confidence: 99%
“…To date, only one study has considered the genetic predisposition to bone mass content (BMC) in premature infants. It was suggested that multiple genes may be involved in the regulation of bone mass during childhood (11).…”
mentioning
confidence: 99%